Cytotoxicity and ROS scavenging potential of Teucrium montanum L. methanolic extracts in HaCaT cells - Topalović, Dijana; Pirković, Andrea; Zbiljić, Miloš; Spremo-Potparević, Biljana; Živković, Lada; Jovanović Krivokuća, Milica; Marčetić, Mirjana (Archives of Pharmacy, 2026)
Teucrium montanum L. (TM) is a perennial species of the Lamiaceae family, traditionally used in folk medicine for its diverse therapeutic properties. Although previous studies have explored the biological activity of TM extracts, their effects on skin cells have not been investigated. This study examined the cytotoxic and antioxidant effects of two methanolic extracts of T. montanum (TM1 and TM2), obtained from serpentinite and limestone, across a concentration range of 12.5–400 µg/mL on human keratinocyte (HaCaT) cells. Both extracts showed a concentration-dependent cytotoxic effect in the MTT assay, with no significant impact on cell survival up to 100 µg/mL. At higher concentrations (200 and 400 µg/mL), cell viability decreased significantly, with TM1 exhibiting greater cytotoxicity than TM2. Antioxidant potential was assessed by the H2DCFDA assay, revealing that neither extract altered basal reactive oxygen species (ROS) levels, but higher concentrations increased ROS formation under H2O2-induced oxidative stress. These results suggest that TM1 and TM2 are well tolerated at lower concentrations, but may induce oxidative stress and cytotoxicity at higher concentrations. The findings highlight the importance of dose optimisation for potential therapeutic or cosmetic applications of TM extracts and further phytochemical characterisation to identify the active constituents responsible for these effects.